ANALISIS SWOT KOPERASI KARYAWAN PT. PERMATA SAWIT MANDIRI - Juli N Simangunsong (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
PT Permata Sawit Mandiri is a private company engaged in oil palm plantations. To improve the welfare of employees and the community around the plantation area, this company established an Employee Cooperative. One of the main strategies implemented by the cooperative is a marketing strategy that focuses on fulfilling the primary needs of employees, such as providing basic necessities (sembako) in the plantation area. The company believes that if basic needs can be met quickly, accurately, at a price that is cheaper than the market price, guaranteed quality, and a continuous supply of goods, then employee welfare will increase. However, in its implementation, the cooperative's marketing strategy is still not running optimally. This can be seen from the frequent occurrence of empty stocks of goods and the less than optimal performance of human resources in the marketing department. Therefore, this study was conducted using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify internal and external factors that affect the cooperative, as well as to formulate a more effective marketing strategy. The results of the study are expected to be the basis for decision making for the development of a better and more sustainable cooperative in supporting the welfare of PT Permata Sawit Mandiri employees.